1984
DOI: 10.3109/00016488409107593
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Nasopharyngeal Carriage of Pneumococci as Related to Pneumococcal Vaccination in Children Attending Day-care Centres

Abstract: A long-term study of nasopharyngeal carriership in 405 children, aged 6 months to 5 years, attending day-care centres was performed. The effect of pneumococcal vaccination was evaluated in a double-blind investigation where the children received either Pneumovax (a 14-valent pneumococcal vaccine) or saline. Nasopharyngeal cultures were taken monthly by a trained nurse during a 2-year follow-up period. No difference in pneumococcal carriage was found between vaccinees and controls. Pneumococci were found in 31.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…Second, it showed poor effectiveness against nonbacteremic or community-acquired pneumonia (163) and against IPD in chronically ill patients (163) and individuals aged 75 years or older (164). Third, it may not prevent nasopharyngeal (NP) colonization (165)(166)(167) or mucosal infections (nonbacteremic pneumonia and otitis media) (168,169). Finally, antibody concentrations after subsequent doses of PPV23 appear to be lower than those after primary vaccination (170,171); this hyporesponsiveness is related to the large amount of PS in PPV23, which is thought to exhaust the memory B-cell pool without replenishment (172).…”
Section: Polysaccharide Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it showed poor effectiveness against nonbacteremic or community-acquired pneumonia (163) and against IPD in chronically ill patients (163) and individuals aged 75 years or older (164). Third, it may not prevent nasopharyngeal (NP) colonization (165)(166)(167) or mucosal infections (nonbacteremic pneumonia and otitis media) (168,169). Finally, antibody concentrations after subsequent doses of PPV23 appear to be lower than those after primary vaccination (170,171); this hyporesponsiveness is related to the large amount of PS in PPV23, which is thought to exhaust the memory B-cell pool without replenishment (172).…”
Section: Polysaccharide Vaccinesmentioning
confidence: 99%
“…Because pneumococcus spreads from the carriage state, the unvaccinated were protected against vaccine-type IPD due to reduction of its carriage in the community after PCV immunization of infants (194). Such herd effects were not observed with the introduction of PPV23, likely because PPV23 was not given to young children, who are the main carriers of pneumococci, and PS vaccines do not reduce carriage of vaccine serotypes (165)(166)(167).…”
Section: Effect Of Pneumococcal Conjugate Vaccines: Serotype Replacemmentioning
confidence: 99%
See 1 more Smart Citation
“…One early study that used a quadravalent vaccine containing ∼30-60 mg of polysaccharide from serotypes 1, 2, 5, and 7 demonstrated reduced colonization with these serotypes [31]. However, more-recent studies that used commercially available 14-and 23-valent pneumococcal polysaccharide vaccines did not demonstrate any influence of immunization on colonization [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…4 Exposure while the child is in day care has also been considered, and the magnitude of its effect has been assessed in terms of either the time spent in day care 5 or the size of the day care group. 2,6 In addition to the actual number of individuals in contact with the child, the nature of contact is assumed to affect intensity of transmission. In the pioneer studies of the 1950s, crowding, and therefore close contacts, were suggested as an important risk factor for pneumococcal transmission and carriage.…”
Section: Introductionmentioning
confidence: 99%